Strengthening Police–Community Relations for Sustainable Public Safety Outcomes - Nesia Oktania (Universitas Negeri Semarang, 2025)
Police–community relations represent a fundamental component of effective law-enforcement systems and sustainable public safety governance. This study examines the dynamics between police agencies and community groups, analyzing how cooperative frameworks, communication strategies, and participatory policing programs influence crime prevention and public trust. Using a mixed-methods approach, the research incorporates five years of crime statistics, surveys from 2,400 residents, and interviews with 52 police personnel and community leaders. Quantitative analysis indicates that neighborhoods with active community–police partnerships experienced a 24% reduction in property crime and a 17% decline in public disturbances. Qualitative findings highlight improvements in mutual trust, reporting willingness, and conflict-resolution outcomes. However, the study also identifies persistent challenges, including inconsistent engagement practices, limited resource allocation, and negative perceptions arising from isolated misconduct incidents. The research concludes that strong police–community partnerships significantly enhance security, reduce crime risks, and strengthen social cohesion. The study contributes to policing science by presenting an integrated model of community-oriented policing supported by empirical evidence and strategic recommendations for sustainable implementation.